LAND-USE CHANGE EFFECTS ON SOIL C AND N TRANSFORMATIONS IN SOILS OF HIGH N STATUS: COMPARISONS UNDER INDIGENOUS FOREST, PASTURE AND PINE PLANTATION - Parfitt R.L.; Scott N.A.; Ross D.J.; Salt G.J.; Tate K.R. (My University, 2003)
Globally, land-use change is occurring rapidly, and impacts on biogeochemical cycling may be influenced by previous land uses. We examined differences in soil C and N cycling during long-term laboratory incubations for the following land-use sequence: indigenous forest (soil age = 1800 yr); 70-year-old pasture planted after forest clearance; 22-year-old pine (Pinus radiata) planted into pasture. No N fertilizer had been applied but the pasture contained N-fixing legumes. The sites were adjacent and received 3-6 kg ha-1 yr-1"volcanic" N in rain; NO3--N leaching losses to streamwater were 5-21 kg ha-1 yr-1, and followed the order forest < pasture = pine. Soil C concentration in 0-10 cm mineral soil followed the order: pasture > pine = forest, and total N: pasture > pine > forest. Nitrogen mineralization followed the order: pasture > pine > forest for mineral soil, and was weakly related to C mineralization. Based on radiocarbon data, the indigenous forest 0-10 cm soil contained more pre-bomb C than the other soils, partly as a result of microbial processing of recent C in the surface litter layer. Heterotrophic activity appeared to be somewhat N limited in the indigenous forest soil, and gross nitrification was delayed. In contrast, the pasture soil was rich in labile N arising from N fixation by clover, and net nitrification occurred readily. Gross N cycling rates in the pine mineral soil (per unit N) were similar to those under pasture, reflecting the legacy of N inputs by the previous pasture. Change in land use from indigenous forest to pasture and pine resulted in increased gross nitrification, net nitrification and thence leaching of NO3--N.
Keywords: 14C; 15N; AMMONIUM; EXTRACTABLE CARBON; LIGNIN; MICROBIAL BIOMASS; NEW ZEALAND; NITRATE; RESPIRATION